Arthroscopic Anterior and Inferior Labral Repair for Traumatic Shoulder Instability - Stephen Marcaccio MD; Rafael Buerba MD/MHS; Justin Arner MD; James Bradley MD (SAGE Publishing, 2024)
Background: Anterior glenohumeral instability is common in the young and athletic population and can develop from a dislocation or subluxation event. Avulsion of the anterior inferior glenoid labrum (Bankart lesion) occurs in over 90% of these events. In patients who have unsuccessful conservative management or present with a high risk for redislocation, surgical intervention is indicated. This video presents our technique for arthroscopic anterior and inferior labral repair. Indications: In addition to those patients who have unsuccessful conservative management, surgical management of anterior glenohumeral instability is indicated in patients who are at high risk for redislocation after an initial instability event. These patients include young age and participation in contact sports. Generally, glenoid bone loss over 25% warrants open bony augmentation, but arthroscopic bony augmentation techniques are evolving. Further, the management of "near-track" lesions, or "on-track" lesions with a small distance to dislocation value, remains controversial. Technique Description: This procedure is performed in the lateral decubitus position. A second anterior portal is created distal and lateral to the first anterior portal, entering the shoulder joint just above the subscapularis. The anterior-inferior labrum is prepared with an arthroscopic elevator, followed by a rasp and superior labral anterior and posterior burr. A suture tape is then shuttled around the labrum and the anchor drilled in the appropriate position at the glenoid rim, not violating the cartilage. Anchor placement occurs from an inferior to a superior fashion until the entire labral injury is repaired. Results: This video presents a technique to achieve arthroscopic fixation of an anterior-inferior labral tear in a young athlete with anterior glenohumeral instability. Patients are taken through 3 phases of rehabilitation before return to sport-specific activities, such as contact sports, around 6 months postoperatively. Return-to-sport rates for contact and collision athletes range from 80% to 100%, with recurrent rates ranging from 5% to 20%. Discussion/Conclusion: Arthroscopic anterior-inferior labral repair is a useful technique for minimally invasive glenohumeral stabilization in indicated patients who have minimal glenoid bone loss. Portal placement, labral mobilization, and glenoid preparation are paramount in optimizing the healing potential of the fixation construct. Patient Consent Disclosure Statement: The author(s) attests that consent has been obtained from any patient(s) appearing in this publication. If the individual may be identifiable, the author(s) has included a statement of release or other written form of approval from the patient(s) with this submission for publication.